Robotics Education For Computer Science Students - Kirandziska, Vesna; Ackovska, Nevena (My University, 2011)
Robotics is an emerging field in the area of intelligent systems. Design, construction and operation of robots are crucial parts of Robotics and this should be the domain of teaching Robotics for students that are introduced to this field for the first time. This paper proposes an approach of teaching Robotics to computer science students. Robotic systems should be taught in four different abstraction levels: a mathematical abstraction level, a model abstraction level and a hardware abstraction level and the hardware itself. Each level is based on the previous, but each shows a different perspective of robotic systems. Mathematical programs, modelling tools and software for controlling real robotic systems, as well as the robot hardware itself, are the tools students have to use while studying Robotics.
Keywords: computer science; education; robotics